(untitled) (Dissertare, 2019)
The purpose of this work is to highlight the role of prosocial behaviors in organizational relational dynamics and analyze the possibilities of activating these behaviors in contexts of this nature, to face labor problems, with special reference to the context represented by the economic and social crisis of Venezuela at the end of the second decade of the 21st century. The work is approached from the perspective of the descriptive and retrospective method, with an existentialist humanist approach, which seeks to describe prosociality as one of the protective factors that can calm the consequences of the crisis in contexts of active participation, within the framework of the venezuelan society. It is concluded that organizational citizenship behaviors, as an expression of prosocial behaviors, can be adopted in the labor spheres, as a coping strategy for the country’s situational conjuncture. In addition, the importance of deepening research in the area under analysis in this work is emphasized.